Local Governance Collaboration Model For Preserving Marine Ecosystem In The Coastal Area of Nusa Lembongan Island, Klungkung Regency, Bali - Ida Ayu Putu Sri Widnyani; I Made Kusna Antara; Nyoman Diah Utari Dewi (Indonesian Association for Public Administration (IAPA), 2018)
The marine ecosystem on the coast of Nusa Lembongan is one of the tourist attractions such as coral reefs, mangrove forests and others. The high number of tourist visiting the island also impacts tourism facilities. Increased tourism also has the opportunity to damage the marine ecosystem. Therefore needs a collaboration among stakeholders in maintaining the sustainability of the marine ecosystem . The purpose of this research is to find out and analyze also to find a collaborative model of stakeholders such as government, private sector, community and traditional institutions in preserving the marine ecosystem in Nusa Lembongan. The research is using a qualitative descriptive approach with determining informants technic is purposive sampling. Local government collaboration model in conserving marine ecosystems by strengthening the role of stakeholders at the local level such as: 1) signing memorandum of understanding for creating regional regulations as a policy of the Klungkung Regency; 2) writing in to a local wisdom (awig-awig) as a local policy of the local wisdom institutions (adat); 3) writing into the policy of the tour operator; 4) implement the Tri Hita Karana concept and creating a memorandum of understanding for all parties.